Nutritional Status of Under Five Years Children in Rangpur Cantonment - Hossain, AKM Alamgir; Ali, ASM Zulfiquer; Nazrina, Sayeda; Hossain, Nusrat (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Nutrition is an important factor because of its role in preventing disease and infant survival and growth. Malnutrition and diseases are interlinked with each other and a great problem in all countries of the developing world. Objectives: To assess the nutritional status of the under five year's children in Rangpur Cantonment. Materials and Methods: This descriptive cross-sectional study was done in Children Welfare Centre (CWC) of Combined Military Hospital (CMH), Rangpur from July to August 2018. A total of 50 under five years children were selected and a structured questionnaire was used keeping the focus on socioeconomic status, dietary habits, hygiene practices, and anthropometric indices of the children. Results: Out of 50 children, 60% were male and 40% were female. About 26% of children were in the 36 to 48 months of age group. About 50% were in the height group of >100 cm, 34.0% were in the height group of 91-100 cm, 16% were in the height group up to 90 cm, 48.0% were in the weight group of 12.1-16 kg, 34.0% were in the weight group of 16 kg, 10%were in the weight group of 10.1-12 kg and 8%were in the weight group below 10 kg. Conclusion: In this study, 20% of cases were stunted and 80% of cases were not stunted and no wasted case was found and the overall prevalence of malnutrition in the Rangpur cantonment was low. A further in-depth study is recommended to draw conclusive inferences. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 168-170